2022
DOI: 10.1186/s12876-022-02139-7
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic retrograde appendicitis therapy versus laparoscopic appendectomy versus open appendectomy for acute appendicitis: a pilot study

Abstract: Background An increasing number of studies have shown the merits of endoscopic retrograde appendicitis therapy (ERAT) in diagnosing and treating acute uncomplicated appendicitis. However, no related prospective controlled studies have been reported yet. Our aim is to assess the feasibility and safety of ERAT in the treatment of acute uncomplicated appendicitis. Methods In this open-label, randomized trial, participants were randomly allocated to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 19 publications
0
10
0
11
Order By: Relevance
“…Retained appendiceal stents are removed by endoscopy. Although data is scarce, in the open-label clinical trial by Shen et al, 26 the reported a stent retention rate was 69%. Establishing indications for appendiceal stent placement and identifying factors associated with recurrent appendicitis and appendiceal stent retention will be critical aims for future studies to improve outcomes of ERAT.…”
Section: Endoscopic Retrograde Appendicitis Therapy and Recurrent App...mentioning
confidence: 98%
See 2 more Smart Citations
“…Retained appendiceal stents are removed by endoscopy. Although data is scarce, in the open-label clinical trial by Shen et al, 26 the reported a stent retention rate was 69%. Establishing indications for appendiceal stent placement and identifying factors associated with recurrent appendicitis and appendiceal stent retention will be critical aims for future studies to improve outcomes of ERAT.…”
Section: Endoscopic Retrograde Appendicitis Therapy and Recurrent App...mentioning
confidence: 98%
“…ERAT has now been widely adopted in China. The technical success (successful intubation of appendix and successful drainage of the appendiceal cavity) and clinical success (improvement in abdominal pain, nausea, and fever) of ERAT is as high as 99% for AUA 21–30. Most ERAT cases in China are performed on an outpatient basis.…”
Section: Endoscopic Retrograde Appendicitis Therapy—safety Indication...mentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Its benefits include minimal invasiveness, convenience, organ preservation, and a low postoperative infection rate, making it favoured among clinicians. 11 Moreover, ERAT has garnered considerable attention because it promptly relieves patients' pain by alleviating appendiceal pressure. 9 Thus, ERAT has gradually been applied in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies included few patients and were mainly from China, making worldwide generalization questionable. The most recent randomized trial published by Shen et al [ 6 ] including 33 patients undergoing ERAT is a “pilot study”, implicitly assuming that a larger study is necessary to confirm its findings in favor of the technique.…”
mentioning
confidence: 99%